Correlation between psychological characteristics and entrepreneurial success: a study of Malay women entrepreneurs / Nurwahida Fuad and Abdul Manaf Bohari - Fuad, Nurwahida; Bohari, Abdul Manaf (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2010)
Nowadays, with the emphasis on knowledge based economy, entrepreneurs hip is an important factor to attain its competitive and dynamic character. It is the driving force for the achievement of economic development and contributes to personal development. Furthermore, firms owned by women entrepreneurs are become vital contribution for economic development in the world nowadays. Women entrepreneurs play an important role in entrepreneurs hip world especially in Small Medium Enterprise (SME) because women are effectively involved in many entrepreneurs sectors. Meanwhile, psychological characteristics of entrepreneurs also have received particular attention all over the world, specifically the need of achievement and locus of control. Thus, the purpose of this study is to investigate the correlation between psychological characteristics (need for achievement and locus of control) and entrepreneurial success among Malay women entrepreneurs in Malaysia. This study was conducted among 150 Malay women entrepreneurs in Malaysia were listed in USAHANITA s online directory. The finding obtained from this study indicated that there was a significant (2 tailed significant) positive correlation between psychological characteristics and entrepreneurial success. Meanwhile, the results indicated that variable need for achievement contributes high influence toward women entrepreneurial success and for this there were suggestions to establish the high level of variables need for achievement.